Drift correction for accurate PRF-shift MR thermometry during mild hyperthermia treatments with MR-HIFU. (17th August 2016) - Bing, Chenchen; Staruch, Robert M.; Tillander, Matti; Köhler, Max O.; Mougenot, Charles; Ylihautala, Mika; Laetsch, Theodore W.; Chopra, Rajiv
Abstract: There is growing interest in performing hyperthermia treatments with clinical magnetic resonance imaging-guided high-intensity focused ultrasound (MR-HIFU) therapy systems designed for tissue ablation. During hyperthermia treatment, however, due to the narrow therapeutic window (41–45 °C), careful evaluation of the accuracy of proton resonant frequency (PRF) shift MR thermometry for these types of exposures is required. Purpose: The purpose of this study was to evaluate the accuracy of MR thermometry using a clinical MR-HIFU system equipped with a hyperthermia treatment algorithm. Methods: Mild heating was performed in a tissue-mimicking phantom with implanted temperature sensors using the clinical MR-HIFU system. The influence of image-acquisition settings and post-acquisition correction algorithms on the accuracy of temperature measurements was investigated. The ability to achieve uniform heating for up to 40 min was evaluated in rabbit experiments. Results: Automatic centre-frequency adjustments prior to image-acquisition corrected the image-shifts in the order of 0.1 mm/min. Zero- and first-order phase variations were observed over time, supporting the use of a combined drift correction algorithm. The temperature accuracy achieved using both centre-frequency adjustment and the combined drift correction algorithm was 0.57° ± 0.58 °C in the heated region and 0.54° ± 0.42 °C in the unheated region. Conclusion: Accurate temperature monitoring of hyperthermia exposures using PRF shift MR thermometry is possible through careful implementation of image-acquisition settings and drift correction algorithms. For the evaluated clinical MR-HIFU system, centre-frequency adjustment eliminated image shifts, and a combined drift correction algorithm achieved temperature measurements with an acceptable accuracy for monitoring and controlling hyperthermia exposures.